Some Kinetic Properties of Arginase in Sheep Spleen Tissue - Kandemir, Fatih Mehmet; Ozdemir, Necmi (Kafkas Univ, Veteriner Fakultesi Dergisi, 2009)
In this study, some kinetic properties of arginase in the sheep spleen tissue was been optimized at first time in our laboratory. The spleen tissues used in the present study were obtained from the Elkas sloughterhause in Elazig. The thiosemicarbazide- diacetylmonoxime urea (TDMU) method was used to measure arginase activity. Protein was measured by the method of Lowry et al. Its was found to be preincubation temperature 58 degrees C, preincubation period 13 min. incubation period 10 min and optimum pH 9.5 for sheep spleen tissues Furthermore, it was found that arginase in sheep spleen tissue was sensitive to different metal ions. It was found that the most effective was Mn+2 from among (Mn+2, Cu+2, Mg+2, Ba+2, Fe+3, Ag-1, Cr+3, Sn+2, Hg+2, Pb+2, Co+2, Ni+2, Zn+2, Cd+2, Lr+1, K+1, Al+3, Mo+6, Na-1 and Ca+2) metal ions. Arginase showed the highest activity in a 2 mM MnCL2 concentration. The enzyme has no activity in presence of Pb+2 and Ag+1 ions. Km of arginase in sheep spleen tissue for arginine were determined tobe 6 mM.
Koyun Dalak Doku Arginazının Bazı Kinetik Özellikleri
Keywords: Arginase; Sheep spleen tissue; Kinetic properties